2019
DOI: 10.1186/s13054-019-2365-1
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Maneuvers and Higher PEEP, the So-Called Open Lung Concept, in Patients with ARDS

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2019. Other selected articles can be found online at https://www.biomedcentral.com/collections/annualupdate2019 . Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http://www.springer.com/series/8901 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
1
40
0
1
Order By: Relevance
“…28 Open lung ventilation (OLV) involves RM and high PEEP administration. 29 Chaney et al 19 do not mention RM in their study and Lellouche et al 20 performed RM after weaning from CPB, Miranda et al 22 applied RM after induction and during the postoperative ICU stay. Therefore, in the last two studies, patients were actually ventilated with the OLV strategy.…”
Section: Discussionmentioning
confidence: 99%
“…28 Open lung ventilation (OLV) involves RM and high PEEP administration. 29 Chaney et al 19 do not mention RM in their study and Lellouche et al 20 performed RM after weaning from CPB, Miranda et al 22 applied RM after induction and during the postoperative ICU stay. Therefore, in the last two studies, patients were actually ventilated with the OLV strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account MV settings, our results showed that ultra-protective ventilation strategy [ 32 ], with significant reductions in V T /IBW (from 5.5 to 4.0 mL/kg), P plat (from 27 to 21 cmH 2 O), ΔP (from 11 to 8 cmH 2 O) and RR (from 22 to 14 breaths/min) was feasible in all patients after ECMO initiation. However, lung ventilation parameters were also within the “protective” ranges before ECMO initiation [ 3 ], with levels of PEEP (from 14 to 13 cmH 2 O) indicating the maintenance of an “open lung” strategy [ 40 , 41 ], even during ECMO. These findings suggest the importance of MP monitoring at the bedside, as lung stress may occur even within acceptable ranges of V T , P plat , and PEEP and might prompt an earlier use of extra-corporeal therapies to reduce the occurrence of VILI.…”
Section: Discussionmentioning
confidence: 99%
“…Other MV parameters that account for MP computation, such as PEEP, V T /IBW, and RR should also be carefully monitored. The lower PEEP values in ICU non-survivors (10 vs. 14 cmH 2 O) could support the open lung strategy [ 40 , 41 , 42 , 43 ]. At the same time, the lower V T /IBW in ICU deaths (3.0 vs. 4.0 mL/kg) might suggest a limit value in V T reduction, even on ECMO [ 9 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, the application of RM has been a topic of debate. Although the use of the open lung concept has been suggested in refractory hypoxaemia, 23 in a multicentre trial examining the use of RM in moderate to severe ARDS, a strategy that included the systematic use of RM was associated with increased mortality. 24 In addition, RMs were used in 32.7% in patients with severe ARDS, which is slightly less than what was found in our survey.…”
Section: Discussionmentioning
confidence: 99%